MECHANICAL PROPERTIES OF SERVOVITE FILMS FORMED IN DURING FRICTION AQUEOUS SOLUTIONS OF CARBOXYLIC ACIDS - V. E. Burlakova; E. G. Drogan; A. I. Tyurin; T. S. Pirozhkova (Advanced Engineering Research, 2018)
Introduction. The effect of the organic component nature in the systematic series of monocarboxylic acids on the tribological characteristics of the brass-steel friction pair in aqueous solutions is described. Dependence of the mechanical-and-physical properties of the antifriction films formed during friction on the nature of the lubricating composition is investigated. The work objectives are to study the applicability of carboxylic acids as an antifriction lubricant component; to assess their effect on the mechanical properties of the servovite film formed under the brass – steel friction.Materials and Methods. Tribological studies of the brass-steel friction pair on the AE-5 end-type friction machine are carried out. Roughness parameters of the servovite  film were determined through the optical profilometry. The microgeometry and the object structure at the nanoscale were considered using atomic force microscopy. The mechanical characteristics of the antifriction film were investigated using the instrument nanoindentation.Research Results. Tribological characteristics of the brass-steel tribocoupling and mechanical-and-physical properties of the servovite film formed during friction in the “brass – aqueous solution of carboxylic acid – steel” system were studied. It is established that the friction factor reduces when increasing the hydrocarbon radical length. The dimensional effects are found in the mechanical and tribological properties of the servovite film formed on the surface of the friction interaction in the carboxylic acids.Discussion and Conclusions. The study results show that the friction interaction on the wearing surface in the aqueous solutions of carboxylic acids forms a nanostructured servovite film which drops the friction factor. Its mechanical, physical and tribological parameters depend on the composition of the model lubricating medium. It is determined that the local mechanical-and-physical properties depend on the method of producing the servovite layer, the load and the size of the deformation zone. The results obtained can be used in the development of lubricants.